Miners and mendicants: A cautionary tale. Issue 2 (April 2019) - Lytle, Murray; Hitch, Michael
Highlights: Mineral resources may be found in areas of missing or corrupt government. There is a correlation between Informal mining and missing or corrupt government. Resource developers may be asked to provide missing social infrastructure. Such alms-giving may create problematic power imbalances. Early detection of missing or corrupt government allows contingency planning. Abstract: This paper posits that the existence of informal miners is indicative of and correlated to government institutionality which is defined as the degree to which local and regional governments are operative in the area of interest. It is further asserted that the degree of government institutionality may impact the infrastructure benefits solicited from resource companies by the affected communities. A mendicant relationship may develop if the infrastructure solicited includes things such as police, justice, medical and educational facilities that are best maintained by local or regional governments. The asymmetry of power between the two parties may subsequently lead to unfulfilled expectations, violence and issues with social license. A database of the incidence of informal mining and the economic freedom indicators for 15 countries is used to correlate informal mining with government insitutionality and the paper offers thoughts for consideration regarding issues to understand and address when considering operations in developing countries.